Implementasi Content and Language Integrated Learning (CLIL) Dalam Keterampilan Komunikasi Lisan dan Tulisan Pada Mata Kuliah English for Communication - Eva Fachriyah; Erma Perwitasari (Peneliti.net, 2023)
The purpose of this study was to describe the application of Content and Language Integrated Learning (CLIL) in English for Communication courses, with an emphasis on spoken and written English communication skills that emphasize learning techniques and learning activities. This study used a descriptive qualitative case study methodology to disclose CLIL-based learning strategies and lecture activities in an English for communication course. Data collected through observation and interviews. The findings of this study indicate that lectures in classes with the English for Specific Purposes (ESP) feature in the English for Communication course can be facilitated and strongly support lectures employing the CLIL approach, which is supported by the curriculum and the development of needs-based teaching materials. The objective of the lecture activities is to improve students' oral and written communication skills, as well as their reading and listening English skills, by integrating a variety of activities to make learning enjoyable and compatible with students' scientific backgrounds